Religious Moderation Values and Moral Messages in the Short Video Lead India: The Tree - Zakia Ulya; Muqni Affan Abdullah; Khairil Fazal (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2025)
The short video Lead India: The Tree presents an inspiring story of unity, tolerance, and social leadership rooted in universal human values. This study aims to analyze the religious moderation values and moral messages embedded in the video and to explore their relevance to multicultural societies. Using a qualitative descriptive approach through content analysis, this study examines the symbols, narratives, and behaviors of the main characters. The findings show that the video reflects four key pillars of religious moderation: national commitment, tolerance, anti-violence, and respect for local traditions. Furthermore, it delivers moral lessons emphasizing social concern, solidarity, and practical action to foster harmony amid diversity. Thus, Lead India: The Tree serves not only as a social campaign medium but also as an effective educational tool for promoting religious moderation and nurturing inclusive community values.